Financial Feasibility Analysis Of Business Broiler with Closed House System (Case Study in Pt. Ciomas Adisatwa, Desa Tuwed, Jembrana, Bali) - I P. V. H., Widana; Sukanata, I W.; Kayana, I G. N. (Jurnal Peternakan Tropika, 2019)
This study aims to determine whether the closed house broiler chicken farms are feasible or not. This research was conducted at the PT. Ciomas Adisatwa located in Tuwed Village, Jembrana, Bali. The type of data used is primary and secondary data which are quantitative and qualitative. The method used in collecting data is observation, interviews, and documentation. The variables observed in this study were broiler production performance and the financial feasibility of broiler farms. The results showed that the average harvest age was 32.61 days with an average weight of 1.75 kg/head, average feed consumption of 3.4 kg/head, depletion rate of 3, 64%, FCR of 1.61, and performance index of 322.15. The results of the financial feasibility analysis show that the broiler chicken business in PT. Ciomas Adisatwa is financially feasible which can be shown by the NPV of Rp. 12.6 billion, IRR 26.55%, Net B/C Rp. 1.74, the Pay Back Period (PBP) can be achieved in a period of 0.74 years, Break Event Point time (BEP) of 4.7 years, BEP production is 1,394,700.18 kg, BEP price is Rp. .19,742.52/kg. Whereas the sensitivity of financial feasibility to increase of feed price decrease of chicken price 6,4% are 10,37% and 6,4% respectively.The conclusion of this study is the performance of the production of broiler chicken farms in the Tuwed Farm owned by PT.Ciomas Adisatwa classified as sufficient and feasible to run financially.   Keywords: Broiler chicken, Closed house, Financial feasibility, Sensitivity.